Effect of Maternal Multiple Micronutrient vs Iron–Folic Acid Supplementation on Infant Mortality and Adverse Birth Outcomes in Rural Bangladesh. Issue 4 (April 2015) - West, Keith P.; Shamim, Abu Ahmed; Mehra, Sucheta; Labrique, Alain B.; Ali, Hasmot; Shaikh, Saijuddin; Klemm, Rolf D. W.; Wu, Lee S.-F.; Mitra, Maithilee; Haque, Rezwanul; Hanif, Abu A. M.; Massie, Allan B.; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT In poor regions of the world, multiple micronutrient (MM) deficiencies are common among pregnant women, along with burdens of low birth weight (LBW), preterm birth, small for gestational age (SGA), stillbirth, infant mortality, and maternal mortality. Several studies have compared the effects of daily, antenatal MMs with iron–folic acid supplementation but have lacked statistical power to determine effects on infant mortality. This cluster randomized trial was performed (2008–2012) in rural Bangladesh to estimate the effects of antenatal MM versus iron–folic acid supplementation on infant mortality and adverse birth outcomes. The efficacy of daily antenatal use of an oral 15-micronutrient supplement was compared with use of an iron–folic acid supplement alone in reducing all-cause infant mortality to age 6 months. The supplements were also assessed for stillbirth, preterm birth, and LBW outcomes and for the relative risk (RR) of being born SGA. Infant mortality was followed through age 12 months. The trial was conducted in a contiguous area in northern Bangladesh. Surveillance included 127, 282 women, of whom 44, 567 became pregnant and delivered 28, 516 live-born infants. Median gestation at enrollment was 9 weeks (interquartile range, 7–12 months). Live-born infants were assessed for size, delivery complications, and morbidity symptoms within 8 hours of birth. Infants were assessed at 1, 3, and 6 months for vital status, anthropometry, breast-feeding status, and recent histories of morbidity, diet, and health care received. All outcomes were assessed on an intention-to-treat basis and adjusted for the cluster-randomized design effect. Among 64, 049 under surveillance in the sectors for iron–folic acid treatment and 63, 233 in the regions for MM supplementation, 22, 814 and 23, 104, respectively, became pregnant. Among the 22, 162 and 22, 405 pregnancies recruited into each group, 22.7% (n = 5037 and 5089, respectively) and 10.6% (n = 2356 and 2378, respectively) ended in induced abortion and miscarriage, respectively. A total of 14, 142 and 14, 374 live-born infants were in the iron–folic acid and MM groups, respectively; 99% were singletons, and all contributed to the 6-month mortality analysis. The MM and iron–folic acid groups did not differ in maternal, obstetric, or socioeconomic characteristics. At 6 months, MM did not significantly reduce all-cause infant mortality, with 764 deaths (54.0/1000 live births) in the iron–folic acid group and 741 deaths (51.6/1000 live births) in the MM group (RR, 0.95; 95% confidence interval [CI], 0.86–1.06; P = 0.36). Relative risks of 0.98 (95% CI, 0.88–1.20) and 0.81 (95% CI, 0.63–1.04) were found for neonatal and postneonatal mortality, respectively. At 12 months, no difference was seen in all-cause mortality, with rates of 58.8 per 1000 live births (832 deaths) and 55.5 per 1000 live births (798 deaths) in the iron–folic acid and MM groups, respectively, and an RR of 0.94 (95% CI, 0.85-1.04). Leading causes of death at younger than 6 months were sepsis (17/1000 live births), prematurity/very LBW (14/1000), and birth asphyxia (14/1000). The RRs of death attributed to sepsis, diarrhea dysentery, and birth asphyxia among infants in the MM versus iron–folic acid groups were 0.79 (95% CI, 0.66–0.96), 0.33 (95% CI, 0.12–0.90), and 1.29 (95% CI, 1.05–1.60), respectively. Multiple micronutrient supplementation did lead to a significant reduction in preterm births (RR, 0.85; 95% CI, 0.80–0.91; P < 0.001) and LBW (RR, 0.88; 95% CI, 0.85–0.91; P < 0.001). Mean duration of gestation at birth was 0.30 weeks (95% CI, 0.21–0.40) longer in the MM than the iron–folic acid group (P < 0.001). No overall effect on mortality to age 6 months was found in infants whose mothers received daily MMs versus iron–folic acid from early pregnancy through 12 weeks postpartum, although differences in risk of adverse birth outcomes were apparent. Antenatal MM supplementation may have affected gestational and fetal nutrition through metabolic pathways other than those regulated by iron and folate. These aspects should be subjects for future research.